Statistical approaches to accelerate the development of long-acting antiretrovirals for HIV pre-exposure prophylaxis. Issue 1 (January 2020) - Glidden, David V.
Abstract : Purpose of review: This review considers statistical issues in the design and analysis of the studies used to develop long-acting formulations of antiretrovirals for pre-exposure prophylaxis (PrEP). Recent finding: An abundant pipeline of products is maturing. Accelerating their evaluation as clinical products requires abandonment of noninferiority standards. Randomized trials should be based on the comparison of principled but innovative estimates of background HIV risk and enrich enrollment for those who do not desire current PrEP products. At every stage of testing, innovative analyses can be applied to help inform and accelerate later studies. Summary: The development of new long-acting PrEP regimens can be accelerated by innovations in design, ingenuity in synthesizing data sources, and application of causal inference methods.